PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS KETERAMPILAN GENERIK SAINS (KGS) - Septa Niti Susanti; Agus Suyatna; Undang Rosidin (Jurnal Pembelajaran Fisika, 2013)
The objective of physic learning as a process is to improve student’s thinking ability. To achieve student’s thinking skill in learning, a method and learning source are needed to develop student’s thinking skill. The use of learning source based on science generic skill (or KGS) is very needed in Ohm’s Law and Kirchoff’s First Law materials, because in these materials students are able to conduct generic skills such as direct observation, indirect observation, awareness about scale, mathematic modeling, and logical inference. These skills are able to apply by conducting a practicum using student’s work sheet (or LKS) based on science generic skill (or KGS) that is able to develop student’s thinking skill in Ohm’s Law and Kirchoff’s First Law materials. This development research used development model adapted from Suyanto with the following stages: 1) need assessment, 2) resource identification, 3) product specification identification, 4) product development, 5) internal test, 6) external test, and 7) production. Based on the test field results conducted with one-shot case study design, the conclusions were that the Ohm’s Law student’s work sheet was not effective to be used as a learning source with the student’s passing percentage of 74.2% and the student’s work sheet of Kirchoff’s First Law was effective to be used as a learning source with the student accomplishment percentage of 83.3%. Achieved indicators of science generic skill (KGS) in Ohm’s Law student’s work sheet were direct observation (98.4%), indirect observation (75.8%), and awareness about scale (100%). Indicators of mathematic modeling and logical inference were not achieved in Ohm’s Law student’s work sheet with percentages of 68.5% and 64.54% respectively. Achieved indicators of science generic skill in student’s work sheet of Kircoff’s First Law were indirect observation (93.3%), awareness about scale (97.5%), and logical inference (76.6%). Mathematic modeling was not achieved in student’s work sheet of Kirchoff’s First Law with 71.6% percentage. Results of attraction and ease questionnaires were 3.07 and 3.26 respectively and they belonged to attracting and very easy criteria.Keywords: Development, LKS, KGS.